Conductive ablation-resistant modified carbon nanotube filling coating sleeve material and preparation method thereof
By using low-filled modified carbon nanotubes as conductive fillers in nitrile rubber cladding material, combined with components such as ablation-resistant fibers and resins, the problems of electrostatic accumulation and thermal insulation performance of existing materials are solved, and the results of both conductivity and ablation resistance are achieved, and the safety and performance of the material are improved.
Patent Information
- Application Number
- CN202510064093.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-15
- Publication Date
- 2025-04-25
AI Technical Summary
The existing nitrile rubber cladding material has safety risks due to electrostatic accumulation. While improving ablation resistance, excessive conductive filler will lead to a degradation of thermal insulation performance, making it difficult to achieve effective electrostatic conduction effect while ensuring ablation and thermal insulation performance.
Through component sorting and surface modification of conductive fillers, low-filling modified carbon nanotubes are used as conductive fillers, combined with components such as nitrile rubber, ablation-resistant fiber/pulp and ablation-resistant resin, and kneaded on the mixer and the mixer to obtain a coated sleeve material that is both conductive and ablation-resistant.
It realizes that while ensuring the ablation and thermal insulation properties of the material, the low-filled conductive filler effectively reduces the material's surface resistivity, releases static electricity, and improves the safety and use performance of the material.
Smart Images

Figure CN119875215A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of ablation-resistant composite materials, and particularly relates to a modified carbon nanotube-filled sheath material having both electrical conductivity and ablation resistance and a preparation method thereof. Background Art
[0002] Nitrile rubber is widely used as the base material of thermal insulation layer and sheath material due to its good bonding performance and molding process. However, due to its good electrical insulation, nitrile rubber is easy to accumulate charge and generate static electricity, so it is easy to generate sparks and explosions during use, which poses a great safety hazard. In addition, in order to improve the ablation resistance of the material, rubber thermal insulation coating materials often introduce special fiber materials such as aramid fiber, aramid pulp, polyimide fiber, etc. that are resistant to high temperature and ablation, but the surface resistivity of this organic fiber is often as high as 10 14 Ω·m or more, it is an electrostatic insulator, which is very likely to cause a large amount of static electricity to accumulate. As we all know, electrostatic discharge is an important external excitation source for solid propellant engine accidents. As an inherent characteristic of propellants, electrostatic sensitivity is difficult to avoid during the preparation process, which leads to greater danger in the production and use of propellants. In addition, during the development of nitrile sheath materials, it was found that the surface resistivity of the material was too large, and it was an electrical insulator, which was not conducive to improving the safety of the propellant charging process. Therefore, in order to further improve the safety of propellant charging, the nitrile sheath material needs to have a certain electrostatic conductivity.
[0003] At present, the main method used in the field of rubber materials is to reduce the surface resistivity of the material to solve the problem of static electricity accumulation in the material. Commonly used conductive fillers include three categories: carbon, metal and composite conductive fillers. However, the sheath material needs to have ablation resistance and thermal insulation properties. Too much conductive filler will lead to the degradation of the ablation resistance and thermal insulation properties of the insulation layer material. Therefore, how to achieve effective static electricity conduction effect of the material at a low filling amount of conductive filler while ensuring the ablation and thermal insulation properties of the sheath has become one of the difficulties in material design. Summary of the invention
[0004] In order to overcome the deficiencies in the prior art, the inventors have conducted intensive research and provided a modified carbon nanotube-filled coating sheath material having both conductivity and ablation resistance and a preparation method thereof. Through component selection and surface modification of the conductive filler, while ensuring the ablation performance and thermal insulation performance of the coating sheath, a low filling amount of conductive filler is used to achieve an effective static conductive effect.
[0005] The technical solution provided by the present invention is as follows:
[0006] In the first aspect, a modified carbon nanotube filling and coating sheath material having both conductivity and ablation resistance is provided, comprising the following components in parts by weight: 100 parts of nitrile rubber, 10 to 15 parts of plasticizer, 10 to 30 parts of modified carbon nanotube masterbatch, 10 to 40 parts of ablation-resistant fiber / pulp, 20 to 60 parts of ablation-resistant resin, 3 to 5 parts of zinc oxide, 1 to 4 parts of stearic acid, 1 to 3 parts of accelerator, and 0.5 to 2 parts of antioxidant; the mass proportion of modified carbon nanotubes in the modified carbon nanotube masterbatch is 10% to 15%.
[0007] In a second aspect, a method for preparing a modified carbon nanotube-filled sheath material having both conductivity and ablation resistance comprises the following steps:
[0008] The carbon nanotubes are added to anhydrous ethanol, and after ultrasonic dispersion, a modifier is added thereto, and ultrasonic treatment is continued to obtain a modified carbon nanotube ethanol solution;
[0009] The modified carbon nanotube ethanol solution and the nitrile rubber latex are mixed and stirred, and a gelling agent is added at the same time, and the gel is washed and dried to obtain a nitrile rubber masterbatch containing the modified carbon nanotubes;
[0010] The nitrile rubber raw rubber and the plasticizer are plasticized in proportion on an open mill to obtain the nitrile rubber plasticized rubber;
[0011] The masterbatch containing modified carbon nanotubes is mixed with nitrile rubber plastic compound, ablation-resistant fiber / pulp, ablation-resistant resin, zinc oxide, stearic acid, accelerator and antioxidant on an internal mixer and an open mixer. After mixing, it is stored at room temperature for a set time and then vulcanized to obtain the coating material.
[0012] A modified carbon nanotube filled sheath material having both conductivity and ablation resistance and a preparation method thereof provided by the present invention has the following beneficial effects:
[0013] (1) According to a modified carbon nanotube-filled sheath material having both conductivity and ablation resistance and a preparation method thereof provided by the present invention, a scheme of reducing the surface resistivity of the sheath by using a low amount of modified conductive filler is adopted. Compared with the traditional conductive filler, the modified carbon nanotubes as conductive filler can effectively reduce the surface resistivity at a low filling amount. When the modified carbon nanotube filling amount is 2.5 parts, the surface resistivity of the sheath material after vulcanization is reduced to 10 9 Below Ω·m, it is an electrostatic subconductor and can effectively release static electricity;
[0014] (2) According to the present invention, a modified carbon nanotube-filled coating sheath material with both conductivity and ablation resistance and a preparation method thereof are provided. Specific modified carbon nanotubes are used to improve the dispersion of carbon nanotubes in the nitrile coating sheath, so that the ablation performance of the material is not affected when the modified carbon nanotubes are filled in a low amount. At the same time, the coating sheath is given a good electrostatic conductive effect, thus overcoming the problem of excessive filling of carbon nanotubes, which leads to a decrease in the ablation resistance of the material.
[0015] (3) According to the present invention, a modified carbon nanotube filling and coating sheath material having both conductivity and ablation resistance and a preparation method thereof are provided, wherein ionic liquid modifiers such as 1-allyl-3-methylimidazole bromide and 1-allyl-3-methylimidazole chloride are used. The ionic liquid as a modifier can effectively improve the dispersibility of the carbon nanotubes in the rubber. At the same time, the ionic liquid itself has conductive properties, which can improve the dispersibility of the carbon nanotubes in the rubber while further enhancing its conductive properties, thereby further reducing the amount of carbon nanotubes used. However, the use of non-conductive modifiers such as polyvinyl pyrrolidone cannot achieve the same effect. BRIEF DESCRIPTION OF THE DRAWINGS
[0016] Figure 1 This is a SEM image of the brittle fracture surface of the sheath material before ablation in Example 1 of the present invention;
[0017] Figure 2 This is a SEM image of the cross section of the ablation layer of the sheath material after ablation in Example 1 of the present invention. DETAILED DESCRIPTION
[0018] The following detailed description of the present invention will make the features and advantages of the present invention more clear and explicit.
[0019] The word “exemplary” is used exclusively herein to mean “serving as an example, example, or illustration.” Any embodiment described herein as “exemplary” is not necessarily to be construed as preferred or advantageous over other embodiments.
[0020] The invention provides a modified carbon nanotube filling and coating sheath material with both conductivity and ablation resistance. The material comprises the following components in parts by mass: 100 parts of nitrile rubber, 10 to 15 parts of plasticizer, 10 to 30 parts of modified carbon nanotube masterbatch, 10 to 40 parts of ablation-resistant fiber / pulp, 20 to 60 parts of ablation-resistant resin, 3 to 5 parts of zinc oxide, 1 to 4 parts of stearic acid, 1 to 3 parts of accelerator, and 0.5 to 2 parts of antioxidant; the mass proportion of the modified carbon nanotubes in the modified carbon nanotube masterbatch is 10% to 15%.
[0021] Preferably, the modified carbon nanotube filling and coating sheath material having both conductivity and ablation resistance comprises the following components in parts by mass: 100 parts of nitrile rubber, 10 to 15 parts of plasticizer, 10 to 20 parts of modified carbon nanotube masterbatch, 10 to 20 parts of ablation-resistant fiber / pulp, 20 to 40 parts of ablation-resistant resin, 3 to 5 parts of zinc oxide, 1 to 3 parts of stearic acid, 1 to 3 parts of accelerator, and 0.5 to 2 parts of antioxidant; the mass proportion of ionic liquid modified carbon nanotubes in the modified carbon nanotube masterbatch is 10% to 15%, and preferably the mass proportion of modified carbon nanotubes in the modified carbon nanotube masterbatch is 10%.
[0022] In a preferred embodiment, the plasticizer is selected from at least one of dibutyl phthalate, dioctyl phthalate or tricresyl phosphate.
[0023] In a preferred embodiment, the modifying agent for modifying the carbon nanotubes is selected from at least one of 1-allyl-3-methylimidazole bromide, 1-allyl-3-methylimidazole chloride, 1-ethyl-3-methylimidazole, or 1-butyl-3-methylimidazole. The mass ratio of the modifying agent to the carbon nanotubes is 3:1 to 1:1.
[0024] In a preferred embodiment, the ablation-resistant fiber / pulp is selected from at least one of aramid fiber / pulp, aramid sulfone fiber, polyimide fiber / pulp, phenolic fiber, poly(p-phenylene benzoxazole) fiber and the like.
[0025] In a preferred embodiment, the ablation-resistant resin is selected from at least one of benzoxazine resin, phenolic resin, phenyl silicone resin, cyanate resin or polyarylacetylene resin.
[0026] In a preferred embodiment, the accelerator is selected from at least one of accelerator TMTD, accelerator DM, accelerator CZ, accelerator TMTM or accelerator M.
[0027] In a preferred embodiment, the antioxidant is selected from at least one of antioxidant MB, antioxidant RD, antioxidant 4010NA, antioxidant 4020 or antioxidant ODA.
[0028] The present invention also provides a method for preparing a modified carbon nanotube filled coating sheath material having both conductivity and ablation resistance, comprising the following steps:
[0029] Step 1: Preparation of modified carbon nanotubes: adding carbon nanotubes to anhydrous ethanol, after ultrasonic dispersion, adding a modifier thereto, and continuing ultrasonic treatment to obtain a modified carbon nanotube ethanol solution;
[0030] The ultrasonic time of carbon nanotubes is 30min-50min, and the power is 100-200W; the ultrasonic time after adding the modifier is determined according to the type of the modifier used, generally 30min-90min, and the power is 100-200W.
[0031] Step 2: Mixing the modified carbon nanotube ethanol solution obtained in step 1 with nitrile rubber latex in a certain proportion, adding sodium chloride gelling agent, washing and drying the gel, and obtaining a nitrile rubber masterbatch containing modified carbon nanotubes;
[0032] Step 3: The nitrile rubber raw rubber and the plasticizer are plasticized on an open mill in proportion, and the roller distance is set to 1mm to 2mm to obtain the nitrile rubber plasticized rubber;
[0033] Step 4: Mix the nitrile rubber masterbatch containing modified carbon nanotubes prepared in step 2 with the nitrile rubber plasticized rubber, ablation-resistant fiber / pulp, ablation-resistant resin, zinc oxide, stearic acid, accelerator and antioxidant prepared in step 3 in one and two stages on an internal mixer and an open mixer. After mixing, store at room temperature for 16 to 24 hours, use a rotorless vulcanizer to measure the positive vulcanization time at different vulcanization temperatures, determine the vulcanization time and vulcanization temperature, and obtain the coating material after vulcanization.
[0034] Example
[0035] Example 1
[0036] A method for preparing a modified carbon nanotube filled sheath material having both conductivity and ablation resistance comprises the following steps:
[0037] Step 1: Add 1 part of carbon nanotubes to anhydrous ethanol and disperse them by ultrasonication for 30 minutes at a power of 100 W. Then add 1.5 parts of 1-allyl-3-methylimidazole bromide and continue ultrasonication for 30 minutes at a power of 200 W to obtain an anhydrous ethanol solution of carbon nanotubes modified with 1-allyl-3-methylimidazole bromide.
[0038] Step 2: Mixing the anhydrous ethanol solution of carbon nanotubes modified by 1-allyl-3-methylimidazole bromide with nitrile rubber latex, adding sodium chloride gelling agent, washing and drying the gel, and obtaining nitrile rubber masterbatch containing modified carbon nanotubes.
[0039] Step 3: The nitrile rubber raw rubber and the plasticizer dibutyl phthalate are plasticized in proportion on an open mixing mill, and the roller distance is set to 1mm to obtain the nitrile rubber plasticized rubber.
[0040] Step 4: On an internal mixer and an open mixer, 115 parts of nitrile rubber plasticized rubber (100 parts of nitrile rubber, 15 parts of plasticizer), 10 parts of aramid fiber, 20 parts of benzoxazine resin, 3 parts of zinc oxide, 1 part of stearic acid, 1 part of antioxidant RD, 1 part of accelerator TMTD, and 10 parts of masterbatch containing modified carbon nanotubes (1 part of 1-allyl-3-methylimidazole bromide modified carbon nanotubes, 9 parts of nitrile rubber) were mixed in the first and second stages. After the mixed rubber was left for 16 hours, the corresponding positive vulcanization time was measured, and then the nitrile sheath material was pressed with a flat vulcanizer. The surface resistivity of the sheath material is 5.2×10 8 Ω·m, linear ablation rate 0.023mm / s.
[0041] The SEM image of the brittle fracture of the sheath material before ablation is shown in Figure 1 It can be seen that the rubber is dense after vulcanization and there is no obvious carbon nanotube agglomeration; the SEM image of the cross section of the ablation layer after ablation is shown in Figure 2 ,It can be seen that the carbon layer is dense after ablation and has good ablation resistance.
[0042] Example 2
[0043] Step 1: Add 1 part of carbon nanotubes to anhydrous ethanol and disperse them by ultrasonication for 30 minutes at a power of 100 W. Then add 1.5 parts of 1-allyl-3-methylimidazole bromide and continue ultrasonication for 30 minutes at a power of 200 W to obtain an anhydrous ethanol solution of carbon nanotubes modified with 1-allyl-3-methylimidazole bromide.
[0044] Step 2: Mixing the anhydrous ethanol solution of carbon nanotubes modified by 1-allyl-3-methylimidazole bromide with nitrile rubber latex, adding sodium chloride gelling agent, washing and drying the gel, and obtaining nitrile rubber masterbatch containing modified carbon nanotubes.
[0045] Step 3: The nitrile rubber raw rubber and the plasticizer dibutyl phthalate are plasticized in proportion on an open mixing mill, and the roller distance is set to 1mm to obtain the nitrile rubber plasticized rubber.
[0046] Step 4: On an internal mixer and an open mixer, 115 parts of nitrile rubber plasticized rubber (100 parts of nitrile rubber, 15 parts of plasticizer), 10 parts of aramid fiber, 20 parts of benzoxazine resin, 3 parts of zinc oxide, 1 part of stearic acid, 1 part of antioxidant RD, 1 part of accelerator CZ, and 15 parts of masterbatch containing modified carbon nanotubes (1.5 parts of 1-allyl-3-methylimidazole bromide modified carbon nanotubes, 13.5 parts of nitrile rubber) are mixed in the first and second stages. After the mixed rubber is left for 16 hours, the corresponding positive vulcanization time is measured, and then the nitrile sheath material is pressed with a flat vulcanizer. The surface resistivity of the sheath material is 9.6×10 7 Ω·m, linear ablation rate 0.041mm / s.
[0047] Example 3
[0048] A method for preparing a modified carbon nanotube filled sheath material having both conductivity and ablation resistance comprises the following steps:
[0049] Step 1: Add 1 part of carbon nanotubes to anhydrous ethanol, and disperse them by ultrasonication for 30 minutes at a power of 100 W. Then, add 1.5 parts of 1-allyl-3-methylimidazole chloride, and continue ultrasonication for 30 minutes at a power of 200 W to obtain an anhydrous ethanol solution of carbon nanotubes modified with 1-allyl-3-methylimidazole chloride.
[0050] Step 2: Mixing the anhydrous ethanol solution of 1-allyl-3-methylimidazole chloride modified carbon nanotubes with nitrile rubber latex, adding sodium chloride gelling agent, washing and drying the gel, and obtaining nitrile rubber masterbatch containing modified carbon nanotubes.
[0051] Step 3: The nitrile rubber raw rubber and the plasticizer dibutyl phthalate are plasticized in proportion on an open mixing mill, and the roller distance is set to 1mm to obtain the nitrile rubber plasticized rubber.
[0052] Step 4: On an internal mixer and an open mixer, 115 parts of nitrile rubber plasticized rubber (100 parts of nitrile rubber, 15 parts of plasticizer), 10 parts of aramid fiber, 40 parts of benzoxazine resin, 3 parts of zinc oxide, 1 part of stearic acid, 1 part of antioxidant RD, 1 part of accelerator TMTD, and 20 parts of masterbatch containing 1-allyl-3-methylimidazole chloride modified carbon nanotubes (2 parts of 1-allyl-3-methylimidazole chloride modified carbon nanotubes, 18 parts of nitrile rubber) are mixed in the first and second stages. After the mixed rubber is left for 16 hours, the corresponding positive vulcanization time is measured, and then the nitrile sheath material is pressed with a flat vulcanizer. The surface resistivity of the sheath material is 1.3×10 8 Ω·m, linear ablation rate 0.039mm / s.
[0053] Example 4
[0054] A method for preparing a modified carbon nanotube filled sheath material having both conductivity and ablation resistance comprises the following steps:
[0055] Step 1: Add 1.5 parts of carbon nanotubes to anhydrous ethanol, and disperse them by ultrasonication for 30 minutes at a power of 100 W. Then add 1.5 parts of 1-allyl-3-methylimidazole chloride, and continue ultrasonication for 30 minutes at a power of 200 W to obtain an anhydrous ethanol solution of carbon nanotubes modified with 1-allyl-3-methylimidazole chloride.
[0056] Step 2: Mixing the anhydrous ethanol solution of 1-allyl-3-methylimidazole-modified carbon nanotubes with nitrile rubber latex, adding sodium chloride gelling agent, washing and drying the gel, and obtaining nitrile rubber masterbatch containing modified carbon nanotubes.
[0057] Step 3: The nitrile rubber raw rubber and the plasticizer dibutyl phthalate are plasticized in proportion on an open mixing mill, and the roller distance is set to 1mm to obtain the nitrile rubber plasticized rubber.
[0058] Step 4: On an internal mixer and an open mixer, 115 parts of nitrile rubber plasticized rubber (100 parts of nitrile rubber, 15 parts of plasticizer), 10 parts of aramid fiber, 30 parts of benzoxazine resin, 3 parts of zinc oxide, 1 part of stearic acid, 1 part of antioxidant RD, 1 part of accelerator DM, and 30 parts of masterbatch containing 1-allyl-3-methylimidazole modified carbon nanotubes (3 parts of 1-allyl-3-methylimidazole modified carbon nanotubes, 27 parts of nitrile rubber) are mixed in the first and second stages. After the mixed rubber is left for 24 hours, the corresponding positive vulcanization time is measured, and then the nitrile coating is pressed with a flat vulcanizer. The surface resistivity of the coating material is 2.9×10 8 Ω·m, linear ablation rate 0.020mm / s.
[0059] Comparative Example
[0060] Comparative Example 1
[0061] On an internal mixer and an open mixer, 115 parts of nitrile rubber plastic compound (100 parts of nitrile rubber, 15 parts of plasticizer dibutyl phthalate), 3 parts of carbon nanotubes, 10 parts of aramid fiber, 20 parts of benzoxazine resin, 3 parts of zinc oxide, 1 part of stearic acid, 1 part of antioxidant RD, and 1 part of accelerator DM were mixed in the first and second stages. After the mixed rubber was left for 24 hours, the corresponding positive vulcanization time was measured, and then a nitrile sheath containing 3 parts of carbon nanotubes was obtained by pressing with a flat vulcanizer. The surface resistivity of the sheath material is 6.3×10 11 Ω·m, linear ablation rate 0.034mm / s.
[0062] Comparative Example 2
[0063] On an internal mixer and an open mixer, 115 parts of nitrile rubber plastic compound (100 parts of nitrile rubber, 15 parts of plasticizer dibutyl phthalate), 8 parts of carbon nanotubes, 10 parts of aramid fiber, 20 parts of benzoxazine resin, 3 parts of zinc oxide, 1 part of stearic acid, 1 part of antioxidant RD, and 1 part of accelerator TMTD were mixed in the first and second stages. After the mixed rubber was left for 24 hours, the corresponding positive vulcanization time was measured, and then a nitrile sheath containing 8 parts of carbon nanotubes was obtained by pressing with a flat vulcanizer. The surface resistivity of the sheath material is 6.7×10 7Ω·m, linear ablation rate 0.102mm / s.
[0064] Comparative Example 3
[0065] A method for preparing a coating material comprises the following steps:
[0066] Step 1: Add 2 parts of carbon nanotubes to anhydrous ethanol, and disperse them by ultrasonication for 30 minutes at a power of 100 W. Then add 2 parts of polyvinyl pyrrolidone and continue ultrasonication for 30 minutes at a power of 150 W to obtain an anhydrous ethanol solution of polyvinyl pyrrolidone-modified carbon nanotubes.
[0067] Step 2: Mix and stir the anhydrous ethanol solution of polyvinyl pyrrolidone-modified carbon nanotubes with nitrile rubber latex, add sodium chloride gelling agent, wash and dry the gel, and obtain a masterbatch containing modified carbon nanotubes.
[0068] Step 3: The nitrile rubber and the plasticizer dibutyl phthalate are plasticized in proportion on an open mixing mill, and the roller distance is set to 1mm to obtain the nitrile rubber plasticized rubber.
[0069] Step 4: On an internal mixer and an open mixer, 115 parts of nitrile rubber plasticized rubber (100 parts of nitrile rubber, 15 parts of plasticizer), 40 parts of masterbatch containing polyvinyl pyrrolidone-modified carbon nanotubes (4 parts of polyvinyl pyrrolidone-modified carbon nanotubes, 36 parts of nitrile rubber), 10 parts of aramid fiber, 20 parts of benzoxazine resin, 3 parts of zinc oxide, 1 part of stearic acid, 1 part of antioxidant RD, and 1 part of accelerator DM were mixed in the first and second stages. After the mixed rubber was left for 24 hours, the corresponding positive vulcanization time was measured, and then the nitrile sheath was pressed with a flat vulcanizer. The surface resistivity of the sheath material is 9.12×10 10 Ω·m, linear ablation rate 0.045mm / s.
[0070] Table 1 Effect data of Examples 1 to 4 and Comparative Examples 1 to 3
[0071] Serial number Surface resistivity / Ω·m <![CDATA[Linear ablation rate / mm·s -1 > Ablation back temperature / ℃ Example 1 <![CDATA[5.2×10 8 ]]> 0.023 39.6 Example 2 <![CDATA[9.6×10 7 ]]> 0.041 40.2 Example 3 <![CDATA[1.3×10 8 ]]> 0.039 41.3 Example 4 <![CDATA[2.9×10 8 ]]> 0.020 42.6 Comparative Example 1 <![CDATA[6.3×10 11 ]]> 0.034 49.2 Comparative Example 2 <![CDATA[6.7×10 7 ]]> 0.102 50.2 Comparative Example 3 <![CDATA[9.12×10 10 ]]> 0.045 48.9
[0072] The present invention has been described in detail above in conjunction with specific implementations and exemplary examples, but these descriptions cannot be understood as limiting the present invention. Those skilled in the art understand that, without departing from the spirit and scope of the present invention, a variety of equivalent substitutions, modifications or improvements may be made to the technical solution of the present invention and its implementation methods, all of which fall within the scope of the present invention. The scope of protection of the present invention shall be subject to the attached claims.
[0073] The contents not described in detail in the specification of the present invention belong to the common knowledge of those skilled in the art.
Claims
1. A modified carbon nanotube filled sheath material having both electrical conductivity and ablation resistance, characterized in that: The invention comprises the following components in parts by weight: 100 parts of nitrile rubber, 10 to 15 parts of plasticizer, 10 to 30 parts of modified carbon nanotube masterbatch, 10 to 40 parts of ablation-resistant fiber / pulp, 20 to 60 parts of ablation-resistant resin, 3 to 5 parts of zinc oxide, 1 to 4 parts of stearic acid, 1 to 3 parts of accelerator, and 0.5 to 2 parts of antioxidant; the weight proportion of the modified carbon nanotubes in the modified carbon nanotube masterbatch is 10% to 15%.
2. The modified carbon nanotube filled sheath material having both conductivity and ablation resistance according to claim 1, characterized in that: The modifying agent for modifying the carbon nanotubes is selected from at least one of 1-allyl-3-methylimidazole bromide, 1-allyl-3-methylimidazole chloride, 1-ethyl-3-methylimidazole or 1-butyl-3-methylimidazole.
3. The modified carbon nanotube filled sheath material having both conductivity and ablation resistance according to claim 2, characterized in that: The mass ratio of the modifier to the carbon nanotubes is 3:1 to 1:
1.
4. The modified carbon nanotube filled sheath material having both conductivity and ablation resistance according to claim 1, characterized in that: The plasticizer is selected from at least one of dibutyl phthalate, dioctyl phthalate or tricresyl phosphate.
5. The modified carbon nanotube filled sheath material having both conductivity and ablation resistance according to claim 1, characterized in that: The ablation-resistant fiber / pulp is selected from at least one of aramid fiber / pulp, aramid sulfone fiber, polyimide fiber / pulp, phenolic fiber or poly(p-phenylene benzoxazole) fiber.
6. The modified carbon nanotube filled sheath material having both conductivity and ablation resistance according to claim 1, characterized in that: The accelerator is selected from at least one of accelerator TMTD, accelerator DM, accelerator CZ, accelerator TMTM or accelerator M.
7. The modified carbon nanotube filled sheath material having both conductivity and ablation resistance according to claim 1, characterized in that: The antioxidant is selected from at least one of antioxidant MB, antioxidant RD, antioxidant 4010NA, antioxidant 4020 or antioxidant ODA.
8. A method for preparing a modified carbon nanotube filled sheath material having both conductivity and ablation resistance as claimed in any one of claims 1 to 7, characterized in that: The steps include: The carbon nanotubes are added to anhydrous ethanol, and after ultrasonic dispersion, the modifier is added thereto. Continue ultrasonic treatment to obtain a modified carbon nanotube ethanol solution; The modified carbon nanotube ethanol solution and the nitrile rubber latex are mixed and stirred, and a gelling agent is added at the same time, and the gel is washed and dried to obtain a nitrile rubber masterbatch containing the modified carbon nanotubes; The nitrile rubber raw rubber and the plasticizer are plasticized in proportion on an open mill to obtain the nitrile rubber plasticized rubber; The masterbatch containing modified carbon nanotubes is mixed with nitrile rubber plastic compound, ablation-resistant fiber / pulp, ablation-resistant resin, zinc oxide, stearic acid, accelerator and antioxidant on an internal mixer and an open mixer. After mixing, it is stored at room temperature for a set time and then vulcanized to obtain the coating material.